Hope Matters in Changing Times - McCarroll, Pamela R. (Toronto journal of theology, 2015)
This article argues that the dominant modern narrative of hope has collapsed in North America and that this is witnessed within the public and ecclesial spheres. While many near the centre of power struggle with hopelessness in the face of this collapse, the article insists that the collapse is both necessary and good. No longer can the modern Western narrative of hope meaningfully address the extent of contemporary crises; no longer can it ignore the multiple oppressions hidden by its dominance. The failure of this narrative of hope opens space for more resilient conceptions of hope to emerge. Affirming the work of Douglas John Hall, the article explores deeper bases for Christian hope through a theology of the cross. Experiences of unexpected possibility in the face of limit, finitude, oppression, and marginalization are held up as reflections of the hope of the cross. Finally, the article demonstrates hope of the cross through a discussion of Jonathan Lear's presentation of Plenty Coups, chief of the Crow Nation, as he leads his people through the colonizing arrival of European settlers to the land of the Crow.